Clathrin and Membrane Microdomains Cooperatively Regulate RbohD Dynamics and Activity in Arabidopsis . Issue 4 (22nd April 2014) - Hao, Huaiqing; Fan, Lusheng; Chen, Tong; Li, Ruili; Li, Xiaojuan; He, Qihua; Botella, Miguel A.; Lin, Jinxing
Abstract : This work used single-particle tracking analysis to detect the dynamics of GFP-RbohD in Arabidopsis. GFP-RbohD spots were found to be mobile with high heterogeneity at the plasma membrane and preferentially assembled into clusters when activated. The results also demonstrated that the internalization of GFP-RbohD occurred via multiple endocytic pathways. Abstract: Arabidopsis thaliana respiratory burst oxidase homolog D (RbohD) functions as an essential regulator of reactive oxygen species (ROS ). However, our understanding of the regulation of RbohD remains limited. By variable-angle total internal reflection fluorescence microscopy, we demonstrate that green fluorescent protein (GFP)-RbohD organizes into dynamic spots at the plasma membrane. These RbohD spots have heterogeneous diffusion coefficients and oligomerization states, as measured by photobleaching techniques. Stimulation with ionomycin and calyculin A, which activate the ROS -producing enzymatic activity of RbohD, increases the diffusion and oligomerization of RbohD. Abscisic acid and flg22 treatments also increase the diffusion coefficient and clustering of GFP-RbohD. Single-particle analysis in clathrin heavy chain2 mutants and a Flotillin1 artificial microRNA line demonstrated that clathrin- and microdomain-dependent endocytic pathways cooperatively regulate RbohD dynamics. Under salt stress, GFP-RbohD assembles into clusters and then internalizes into the cytoplasm. Dual-color fluorescence cross-correlation spectroscopy analysis further showed that salt stress stimulates RbohD endocytosis via membrane microdomains. We demonstrate that microdomain-associated RbohD spots diffuse at the membrane with high heterogeneity, and these dynamics closely relate to RbohD activity. Our results provide insight into the regulation of RbohD activity by clustering and endocytosis, which facilitate the activation of redox signaling pathways.